Jean Giono and the reinvention of the Odyssey in the French postwar literature - Lopes da Costa, Lorena (História: Questões e Debates, 2019)
This paper aims to analyze the relation between war, experience and fiction, through Naissance de l’Odyssée, a French rewriting of the Odyssey. Jean Giono (1895 - 1970), in return from The Great War, chooses epic poetry as a support to elaborate the challenges of the conflit and to put the tradition into question. The sources are Giono’s literature, in particular Naissance de l’Odyssée, novel published in 1930, as well as his war writings and correspondence.